Efficiency in Polish listed commercial banks: a DEA approach - Czerwonka, Leszek (Efektywność polskich giełdowych banków komercyjnych: podejście DEA, 2019)
The subject of the research presented in this paper is the efficiency of key commercial banks in Poland. The research sample includes 12 banks listed on the Warsaw Stock Exchange, which hold over 80% of the assets of the entire commercial banks sector in Poland. The research period is 2013-2018. The aim of the research was to examine whether the largest commercial banks are more efficient than the others and to determine the main reasons for the inefficiency of commercial banks. Data Envelopment Analysis (DEA) was used as the research method. The obtained results indicate that the average efficiency is 0.903. It turns out that the largest banks are on average quite efficient and do not have much room for improvement. In the case of large banks, the average technical efficiency PE is 0.96, while in the case of pure technical efficiency PTE it is as high as 0.99. This indicates that the largest Polish banks manage their resources very efficiently
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 7-18
Keywords: banking; commercial banks; efficiency; Data Envelopment Analysis; DEA; bankowość; banki komercyjne; efektywność